Connection between UML use case diagrams and UML class diagrams: A matrix proposal - Alturas, B. (International Journal of Computer Applications in Technology, 2023)
In recent years, the UML language has been one of the most used to conduct information system analysis and design. Being an object-oriented technique, UML provides a vast set of diagrams, in order to represent the various abstractions of the system, of which the most used are the use-case diagram and the class diagram. Often, in the modelling of less complex systems, only these two diagrams are used, where one represents the functionalities of the system (use case diagram) and the other the static structure of the system (class diagram). However, it is often difficult to make the connection between the two diagrams, and mainly, it is difficult to verify when one matches the other. In order to solve this problem, a matrix is proposed that links the two diagrams, using a case study to verify the utility of the matrix.